Nuremberg: Past, Present and Future - Christopher J. Dodd (Washington University Global Studies Law Review, 2007)
Through historical and personal reflection, these remarks detail the unprecedented conditions of the Nuremberg trials. In addition, the paper explores the historical and modern impact of the principles of the Nuremberg trials.
Keywords: Nuremberg War Crime Trials; Nuremberg; Germany; 1945-1949; Human rights; Due process of law; Right to fair and impartial trial; International; Dodd; Christopher J.